2018
DOI: 10.1002/pssa.201800553
|View full text |Cite
|
Sign up to set email alerts
|

Combined Temperature Radiation Effects and Influence of Drawing Conditions on Phosphorous‐Doped Optical Fibers

Abstract: This work focuses on the effects of high dose ionizing radiation, up to 10 MGy(SiO2), on P‐doped multimode optical fibers (OF) at different irradiation temperatures. The investigation is based on two complementary experimental techniques: radiation‐induced attenuation (RIA) measurements and electron paramagnetic resonance (EPR). The latter technique allows measuring the P1, P2, metastable‐POHC and stable‐POHC defects. Three OF samples are drawn from the same preform to evaluate the influence of changing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The two bands identified in the ULL-PSC sample were close to the ones observed by Kashaykin et al [ 19 ]. A major difference concerns the RIA level reached at 1.55 µm in the ULL-PSC OF.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The two bands identified in the ULL-PSC sample were close to the ones observed by Kashaykin et al [ 19 ]. A major difference concerns the RIA level reached at 1.55 µm in the ULL-PSC OF.…”
Section: Resultssupporting
confidence: 87%
“…The P1 paramagnetic structure corresponds to a P atom bonded to three oxygen atoms and hosting an unpaired electron [ 18 ]. This point defect is associated with an absorption band around 0.79 eV (~1570 nm, FWHM of 0.29 eV), which is mostly responsible for the IR-RIA at both telecommunications wavelengths, even at larger doses than the ones considered in this article [ 19 ]. The P1 defect is very stable at room temperature, explaining how no recovery was observed in our test conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, at earlier times, where most of the diagnostics have to operate, the RIA levels could be higher than in the P-doped optical fiber due to the generation of room temperature metastable defects with strong absorption levels. [14][15][16][17] To overcome the complexity to study the fibers' response at the shortest times, it is possible to lower the irradiation temperature (LNT in our experimental conditions), thereby slowing down the decay kinetics of these metastable defects. Decreasing the irradiation temperature allows studying the RT metastable defect contribution (impacting at time <1 ms at RT) even with a temporal resolution around hundreds of milliseconds.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility to change the detection threshold is to shift the probe wavelength from 1550 nm to the ultraviolet (UV) or visible domains, where the fiber is more radiation sensitive. Indeed, it has been shown that even if the point defects at the origin of the RIA will be different than at 1550 nm (P1 defects [ 20 ]), the P-doped fibers still present some interesting dosimetry properties at around 300 nm (where the P2 defect contribution is preponderant [ 20 , 24 , 25 ]), and at around 650 nm (where the phosphorus-oxygen hole centers (POHC) defects are the main contributors [ 20 , 24 , 25 ]), with RIA kinetics being dose rate and temperature (0 to 50 °C) independent at low doses (<100 Gy). The P2 defects are associated with an absorption band that peaked at 275 nm (4.5 eV, FWHM = 1.27 eV), whereas POHC have absorption bands at 563 nm (2.2 eV, FWHM = 0.35 eV) and 496 nm (2.5 eV, FWHM = 0.63).…”
Section: Discussionmentioning
confidence: 99%